A Note on Omitting Types in Propositional Logic - Kolman, Oren (Armenian Journal of Mathematics, 2015)
Analogues of the classical omitting types theorems of first-order logic are proved for propositional logic. For an infinite cardinal $κ$, a sufficient criterion is given for the omission of $κ$-many types in a propositional language with $κ$ propositional variables.